Optimization of the Samapta Two-Wheel Patrol to Prevent Motor Vehicle Theft in the Jurisdictions of Grobogan Police Resort - Mahari, Zhoffi (Advances in Police Science Research Journal, 2024)
The author’s final project raises the issue of “Why is the performance of the two-wheeled patrol unit in preventing the occurrence of motor vehicle theft at the Grobogan Police Resort not optimal?”. The final project aims to compare the theory and practice in each implementation of the two-wheeled patrol and find efforts or ways to optimize the implementation of two-wheeled patrols carried out by the Grobogan Police Satsamapta in preventing the occurrance of stolen crimes in the jurisdiction of the Grobogan Police. This research uses a qualitative approach with the type of case study research by conducting several limited observation methods, interviewing resource persons and reviewing resource persons, and reviewing research documents. This research uses management theory and SDO theory as well as concepts listed in the laws and regulations governing Satsamapta’s two-wheeled patrol procedures. Satsamapta unit of the Grobogan Police in carrying out two-wheeled patrols to prevent the occurrence of motor vehicle theft is still considered with the SOP. This implementation, it’s also following the ideal division of patrol hours and patrol squads that have been set. The patrols carried out are still a combination of two-wheeled vehicles and four vehicles. The two-wheeled patrol route is only based on preliminary data from the Grobogan Police Intelligence unit and is not based on the development of the actual situation. The supervision carried out by the leadership on the implementation of the Grobogan Police Satsamapta is still relatively low. The ability of members of the Grobogan Police Satsamapta in carrying out two-wheeled patrols is still very minimal, judging from the number of members who have attended vocational education, especially in the field of patrols and there are still members who commit violations in carrying out their duties. Therefore, efforts are needed to optimize the implementation of two-wheeled patrols of the Grobogan Police Satsamapta in preventing stolen crimes through a reward and punishment system for members, enforcing SOP for the implementation of two-wheeled patrols, improving organizational management providing training for members and strengthening supervision from the leadership.